2014
DOI: 10.1167/iovs.13-13522
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Associations and Dynamic Process Motility in Perivascular Myeloid Cells of the Mouse Choroid: Implications for Function and Senescent Change

Abstract: Resident myeloid cells demonstrated close but dynamic physical interactions with choroidal vessels, indicative of constitutive immune-vascular interactions in the normal choroid. These interactions may alter progressively with aging, providing a basis for understanding age-related choroidal dysfunction underlying AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 49 publications
5
28
0
Order By: Relevance
“…Real-time movies of the CX3CR1 GFP/+ mouse demonstrate that these macrophage processes are constantly sampling the environment in fulfillment of their role as sentinels and housekeepers. 30 The study also demonstrated that these dendritiform myeloid cells were perivascular and touched the choroidal vessels, 31 which we also observed in human choroid (Supplementary Movie S1). …”
Section: Discussionsupporting
confidence: 67%
“…Real-time movies of the CX3CR1 GFP/+ mouse demonstrate that these macrophage processes are constantly sampling the environment in fulfillment of their role as sentinels and housekeepers. 30 The study also demonstrated that these dendritiform myeloid cells were perivascular and touched the choroidal vessels, 31 which we also observed in human choroid (Supplementary Movie S1). …”
Section: Discussionsupporting
confidence: 67%
“…D), suggesting that MACs have closer engagement with tube forming cells as part of their supportive role. MACs behavior when cocultured with endothelial cells suggests a potential role for them acting as perivascular macrophages, supporting the endothelium that makes up the vasculature, in part, by sharing close immune‐vascular interactions . This phenomenon is under further investigation.…”
Section: Discussionmentioning
confidence: 89%
“…Choroidal vessels are labeled by cardiac perfusion of an aqueous solution containing 1,19-dioctadecyl-3,3,39,39-tetramethylindocarbocyanine perchlorate (DiI, D-282, Invitrogen/Molecular Probes, Carlsbad, CA), a lipophilic dye that incorporates into membranes of endothelial cells revealing the structure of choroidal vessels as previously described (11). Briefly, experimental mice were euthanized by carbon dioxide inhalation and the thoracic cavity opened to expose the heart.…”
Section: Direct Labeling and Visualization Of Choroidal Vesselsmentioning
confidence: 99%
“…Dysfunction in choroidal macrophages has been linked to choroidal vascular alterations detected in aging and in AMD. Altered macrophage morphology and distribution have been correlated with attenuation of the choriocapillaris in the aged mouse choroid (11), and increased density and expression of activation markers in macrophages have been documented with the onset of AMD in human eyes (14), suggesting a causal relationship between macrophage changes and vascular loss. The implication of choroidal vascular loss as a driver of drusen accumulation and RPE disruption in AMD pathogenesis (15)(16)(17) have prompted strategies aimed at maintaining choroidal vascular health and improving vascular supply to the outer retina (18,19), but the intrinsic mechanisms that maintain vascular and RPE integrity in the choroid have not been elucidated, limiting translational efforts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation